Promising Option for Treatment of Striae Alba: Fractionated Microneedle Radiofrequency in Combination with Fractional Carbon Dioxide Laser - Farahnaz Fatemi Naeini; Shadi Behfar; Bahareh Abtahi-Naeini; Shima Keyvan; Mohsen Pourazizi (Dermatology Research and Practice)
Background. A consistent treatment has not been proposed for treatment of Striae Alba (SA). The present study was designed to compare the fractionated microneedle radiofrequency (FMR) alone and in combination with fractional carbon dioxide laser (FMR + CO2) in the treatment of SA. Methods. Forty-eight pairs of SA from six patients were selected. Right or left SAs were randomly assigned to one of the treatment groups. The surface area of the SA before and after treatment and clinical improvement using a four-point scale were measured at the baseline, after one and three months. Results. The mean age of the patients was 30.17±5.19 years. The mean difference of the surface area between pre- and posttreatment in the FMR + CO2 group was significantly higher than that in the FMR group (p=0.003). Clinical improvement scales showed significantly higher improvement in the FMR + CO2 group than in the FMR group in the first and second follow-up (p=0.002 and 0.004, resp.). There were no major persistence side-effects in both groups. Conclusions. The results showed that FMR + CO2 laser was more effective than FMR alone in the treatment of SA.